التحول الديموغرافي للأسر الحاكمة بالمغرب الأوسط القرن 2-6هـ/8-12م - قاسمي, فوزية; عشي, علي (جامعة الوادي - University of Eloued, 2022)
يعالج موضوع التحول الديموغرافي للأسر الحاكمة في المغرب الأوسط، دراسة التزايد الديموغرافي لدى بني تلكات الصنهاجيين وانعكاساته على صنهاجة المغرب الأوسط، باعتبارهم قوة عددية فاقت حسب المؤشرات التزايد العام للقبيلة. ثم تراجع هذا التزايد حين تحولت الأسرة التلكاتية من عائلة حاكمة موحدة كثيرة الأفراد تكونت من الآباء والأبناء والأعمام في بلاد صنهاجة، إلى أسرة متفرقة بين إفريقية والمغرب الأوسط منذ الانتقال من نظام القبيلة إلى حكم بلاد المغرب سنة 361هـ/972م. ولهذا كان لا بد من تتبع مراحل تطور هذا التحول الديموغرافي من معطيات المصادر التاريخية التي تم التوصل من خلالها إلى عوامل التحكم في هذا التغير ونتائجه بالنسبة لصنهاجة القبيلة في المغرب الأوسط، وعلى مستوى البيت التلكاتي. The subject of demographic transformation of the ruling families in the Middle Maghreb deals with the study of the demographic growth among the Banno talkate Sanhajis and its repercussions on the Sanhaja of the Middle Maghreb, as they constitute a numerical strength that, according to indicators, exceeded the general growth of the tribe. Then this increase declined when the Talkatic family was transformed from a united ruling family with many individuals consisting of fathers, sons and uncles in the country of Sanhaja, to a family separated between Afriqua and the Middle Maghreb since the transition from the tribal system to the rule of the Maghreb in 361AH/972AD. Therefore it was necessary to trace the stages of development of this demographic transformation from the data of historical sources through which the factors controlling this change and its consequences were reached for the Sanhaja tribe in the Middle Maghreb and at the level of the Talkati house.
بنو تلكات الصنهاجيين-نموذجا
مقال
Keywords: بنو تلكات؛ صنهاجة؛ الأسرة الحاكمة؛ التحول الديموغرافي؛ المغرب الأوسط; Banno talkate; Sanhaja; The ruling family; Demographic transformation; Middle Maghreb